Conductive polymer solution and use thereof
By using a conductive polymer solution with a pH of 1.5~5.0, containing a combination of polythiophene and epoxy, the challenges of existing capacitors in increasing capacity and reducing ESR are solved, achieving long-term retention of high capacity and low ESR.
Patent Information
- Application Number
- CN202380062793.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-29
- Filing Date
- 2023-08-25
- Publication Date
- 2025-03-28
AI Technical Summary
Existing conductive polymer capacitors have challenges in improving capacitor capacity and reducing equivalent series resistance (ESR), especially in maintaining heat resistance and durability of low ESR characteristics.
A conductive polymer solution having a pH of 1.5 to 5.0 is provided, which comprises polythiophene, an epoxy compound having at least 2 epoxy groups and water, and a conductive polymer film and an electrolytic capacitor are prepared by a specific composition ratio and treatment method.
An electrolytic capacitor that provides high capacity and maintains low ESR characteristics for a long time is realized, improving the chemical stability and heat resistance of the capacitor.
Smart Images

Figure CN119731263A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive polymer solution, a conductive polymer film obtained by drying the conductive polymer solution, and uses thereof. Background Art
[0002] As one type of electrolytic capacitor, a conductive polymer capacitor is known, which is a capacitor using a conductive polymer for an electrolyte.
[0003] As a conductive polymer aqueous solution for producing such a conductive polymer capacitor, a conductive polymer solution containing a polythiophene-based self-doped conductive polymer and Conductive polymer aqueous solutions of oxazoline compounds (for example, Patent Document 1) and the like.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2020-7519 Summary of the invention
[0007] Problems to be solved by the invention
[0008] One embodiment of the present invention provides a conductive polymer solution capable of providing an electrolytic capacitor having high capacitance and low ESR (equivalent series resistance) characteristics.
[0009] Solutions to the problem
[0010] The present inventors have conducted intensive studies and have found that the following conductive polymer solution can solve the above-mentioned problems, thereby completing the present invention.
[0011] That is, one embodiment of the present invention relates to a conductive polymer solution, a conductive polymer film, and an electrolytic capacitor using the conductive polymer solution as described below.
[0012] A conductive polymer solution having a pH of 1.5 to 5.0, the solution comprising: 0.01 to 10% by mass of a polythiophene (A) comprising at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), 0.001 to 20% by mass of an epoxy compound (B) having at least two epoxy groups, and water.
[0013]
[0014] In the general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1.
[0015] Effects of the Invention
[0016] According to one embodiment of the present invention, a conductive polymer solution capable of providing an electrolytic capacitor having a high capacitance and low ESR characteristics can be provided. DETAILED DESCRIPTION
[0017] Hereinafter, one embodiment of the present invention will be described in detail. It should be noted that, in this specification, "A to B" indicating a numerical range means "A or more and B or less" unless otherwise specified.
[0018] In the field of electrolytic capacitors, along with the increase in speed and frequency of electronic equipment, there is a strong demand for electrolytic capacitors that have a long life, high capacity, and low ESR characteristics.
[0019] Compared with capacitors of the type that do not use a conductive polymer in an electrolyte, conductive polymer capacitors show low ESR characteristics, low temperature characteristics, and excellent stability.
[0020] As a conductive polymer, polythiophene-based conductive polymers are useful in practical use from the perspective of chemical stability. Therefore, it is necessary to improve the conductive polymer composition described in Patent Document 1 to further improve capacitor characteristics (for example, the height of capacitor capacitance).
[0021] Specifically, as one of the improvement strategies, a method of acidifying the liquid of the conductive polymer composition is envisioned. On the other hand, when the liquid of the conductive polymer aqueous solution of Patent Document 1 is acidified, there is a possibility that the conductive polymer aqueous solution may be acidified. The problem that the oxazoline-based water-soluble polymer aggregates and causes the physical properties (e.g., low ESR characteristics, etc.) required for the conductive polymer composition used in the original capacitor to be lost is not easy to improve. In addition, when the liquid of the conductive polymer aqueous solution of Patent Document 1 is acidified, the conductive polymer aqueous solution containing Since water-soluble polymers of oxazoline groups are prone to aggregation, the conductive polymer composition described in Patent Document 1 has the disadvantage that it is difficult to use as an electrolyte for a hybrid capacitor. In addition, although the electrolytic capacitor obtained by using the conductive polymer composition described in Patent Document 1 has a low initial surface resistance value (low ESR), there is still room for improvement in heat resistance and durability (the property of being able to maintain low ESR for a long time).
[0022] The purpose of this embodiment is to provide a conductive polymer solution that can provide an electrolytic capacitor with high capacity and low ESR characteristics. In detail, it relates to a conductive polymer solution showing a specific pH, the solution comprising: a polythiophene containing a specific structural unit, a compound having a specific number of epoxy groups, and water. In addition, this embodiment relates to a method for manufacturing a conductive polymer film, the method comprising: applying the conductive polymer solution to a substrate and drying it. In addition, this embodiment relates to a method for manufacturing an electrolytic capacitor, the method comprising: covering the surface of the dielectric oxide film of the anode body forming the dielectric oxide film with the conductive polymer solution, and heating it to dry it. In addition, this embodiment, by having the above-mentioned structure, also has the advantage of being able to provide a conductive polymer solution, and the conductive polymer solution can provide an electrolytic capacitor that can maintain high capacity and low ESR characteristics for a long time.
[0023] It should be noted that, in this specification, "electrolytic capacitor" refers to a capacitor including a dielectric layer formed by an oxide film containing a metal (e.g., aluminum, etc.), including solid electrolytic capacitors and hybrid capacitors. It should be noted that, in this specification, a solid electrolytic capacitor refers to a capacitor whose electrolyte is a solid. In addition, in this specification, a hybrid capacitor refers to a capacitor whose electrolyte is a hybrid electrolyte formed by a fusion of a conductive polymer and an electrolyte.
[0024] In addition, in this specification, a "solid electrolytic capacitor" may be referred to as a "solid electrolytic capacitor element", and a "hybrid capacitor" may be referred to as a "hybrid capacitor element".
[0025] The present embodiment is a conductive polymer solution having a pH of 1.5 to 5.0, the solution comprising: 0.01 to 10% by mass of a polythiophene (A) comprising at least one structural unit selected from the structural unit represented by the following general formula (1) and the structural unit represented by the following general formula (2), 0.001 to 20% by mass of an epoxy compound (B) having at least two or more epoxy groups, and water.
[0026]
[0027] [In the general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1.]
[0028] In addition, in this specification, the composition containing the polythiophene (A) and the epoxy compound (B) is also referred to as a conductive polymer composition. The conductive polymer solution can also be considered to be a solution containing the conductive polymer composition.
[0029] The linear or branched alkyl group having 3 to 6 carbon atoms is not particularly limited, and examples thereof include n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, cyclopentyl, n-hexyl, 2-ethylbutyl, and cyclohexyl.
[0030] Regarding the above R 2 , from the viewpoint of film-forming properties, a hydrogen atom, a methyl group, an ethyl group, or a fluorine atom is preferred.
[0031] In the general formulae (1) and (2), m represents an integer of 1 to 10, and is preferably an integer of 1 to 6, more preferably an integer of 1 to 4, and even more preferably 2 or 3 from the viewpoint of film-forming properties.
[0032] In the above general formulae (1) and (2), n represents 0 or 1, and n is preferably 1 from the viewpoint of excellent conductivity.
[0033] The structural unit represented by the above formula (2) represents the doping state of the structural unit represented by the above formula (1).
[0034] Dopants that cause insulator-metal transfer due to doping can be divided into acceptors and donors. The former enters near the polymer chain of the conductive polymer by doping, and takes away π electrons from the conjugated system of the main chain. As a result, positive charges (holes) are injected into the main chain, so it is also called a p-type dopant. In addition, the latter in turn provides electrons to the conjugated system of the main chain, and the electrons move in the conjugated system of the main chain, so it is also called an n-type dopant.
[0035] The dopant in this embodiment is a sulfonic group or a sulfonate group covalently bonded to the polymer molecule, and is a p-type dopant. A polymer that can generate conductivity without adding a dopant from the outside is called a self-doping polymer.
[0036] The pH of the conductive polymer solution of this embodiment is 1.5 to 5.0, preferably 2.0 to 4.0, more preferably 2.5 to 3.5, further preferably 2.75 to 3.25, and particularly preferably 3.0. Based on this structure, it has the advantage of being able to provide an electrolytic capacitor showing low ESR characteristics. It should be noted that the pH of the conductive polymer solution can be controlled by the type and content of the compound (D) that can form an ion pair with the sulfonic acid group described later.
[0037] The polythiophene (A) of the present embodiment can be produced by polymerizing a thiophene monomer represented by the following general formula (4) in water or an alcohol solvent in the presence of an oxidizing agent, and then performing an acid treatment as necessary.
[0038]
[0039] [In the general formula (4), M represents a hydrogen ion or a metal ion. 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1.]
[0040] The metal ion represented by M in formula (4) is not particularly limited, and examples thereof include transition metal ions, noble metal ions, non-ferrous metal ions, alkali metal ions (eg, Li ions, Na ions, and K ions), and alkaline earth metal ions.
[0041] When the polymer obtained by polymerizing the thiophene monomer represented by the general formula (4) is a metal salt, M is converted into a hydrogen ion by subjecting the obtained metal salt polymer to an acid treatment.
[0042] The thiophene monomer represented by the general formula (4) is not particularly limited, and specific examples thereof include 6-(2,3-dihydro-thieno[3,4-b][1,4]dihydro- 6-(2,3-dihydro-thieno[3,4-b][1,4]diol)-1-sulfonic acid Sodium 6-(2,3-dihydro-thieno[3,4-b][1,4]diol)-1-sulfonate 6-(2,3-dihydro-thieno[3,4-b][1,4]diol)-1-sulfonate Potassium 8-(2,3-dihydro-thieno[3,4-b][1,4]diol)-1-sulfonate 8-(2,3-dihydro-thieno[3,4-b][1,4]diol)-1-sulfonic acid Sodium 8-(2,3-dihydro-thieno[3,4-b][1,4]diol)-1-sulfonate Potassium 2-oxo-1-octanesulfonate, 3-[(2,3-dihydrothieno[3,4-b]-[1,4] ... Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dihydrothieno[3,4-b]-[1,4]diol] Potassium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxadiene]-1-propanesulfonate Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dihydrothieno[3,4-b]-[1,4]diol]-1-methyl-1-propanesulfonate Sodium 1-ethyl-1-propanesulfonate, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dihydrothieno[3,4-b]-[1,4]diol] Sodium 1-propyl-1-propanesulfonate, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]di Sodium 1-butyl-1-propanesulfonate, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]di Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dihydrothieno[3,4-b]-[1,4]diol]-1-pentyl-1-propanesulfonate Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dihydrothieno[3,4-b]-[1,4]diol]-1-hexyl-1-propanesulfonate Sodium 1-isopropyl-1-propanesulfonate, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]di Sodium 1-isobutyl-1-propanesulfonate, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]di Sodium 1-isopentyl-1-propanesulfonate, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dihydrothieno[3,4-b]-[1,4]diol] Sodium 1-fluoro-1-propanesulfonate, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]di Potassium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dihydrothieno[3,4-b]-[1,4]dioxadienesulfonate] 1-methyl-1-propanesulfonic acid, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]di 1-methyl-1-propanesulfonic acid ammonium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]di 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dihydro- Sodium 4-[(2,3-dihydrothieno[3,4-b]-[1,4]diol]-1-butanesulfonate Potassium 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxadienesulfonate Sodium 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dihydrothieno[3,4-b]-[1,4]diol] Potassium 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dihydrothieno[3,4-b]-[1,4]diol]-1-methyl-1-butanesulfonate sodium 1-fluoro-1-butanesulfonate, and 4-[(2,3-dihydrothieno[3,4-b]-[1,4]di [(2-((((((((((((((((((-((-1-fluoro-1-butanesulfonate( ...-1-fluoro-2-yl(methoxy-1-methoxy-1-
[0043] The electrical conductivity of the polythiophene (A) of the present embodiment is not particularly limited, but is preferably 10 S / cm or more as the electrical conductivity in a film state.
[0044] In addition, as for the polythiophene (A) of this embodiment, what is synthesized based on known information can be used.
[0045] In the conductive polymer solution of the present embodiment, the content of the polythiophene (A) comprising at least one structural unit selected from the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2) is characterized by being 0.01 to 10% by mass, but from the viewpoint of being able to provide an excellent low-ESR electrolytic capacitor, it is preferably 0.05 to 8% by mass, and more preferably 0.1 to 7% by mass.
[0046] The epoxy compound (B) is not particularly limited, and is preferably a compound in which one molecule of a polyol is bonded to at least two molecules of an alcohol having one epoxy group via an ether bond, and more preferably a compound in which one molecule of a polyol is bonded to two molecules of an alcohol having one epoxy group via an ether bond. This configuration has the advantage of being able to provide an electrolytic capacitor showing low ESR characteristics. The epoxy compound (B) is preferably a compound that does not contain a silicon atom.
[0047] The polyol is not particularly limited, but from the viewpoint of providing an electrolytic capacitor having low ESR characteristics, for example, a monohydric to pentahydric alcohol is preferred, a monohydric to trihydric alcohol is more preferred, and a dihydric alcohol is further preferred.
[0048] The alcohol having an epoxy group is not particularly limited, but from the viewpoint of providing an electrolytic capacitor having low ESR characteristics, for example, glycidol is preferred.
[0049] As the above-mentioned epoxy compound (B), there is no particular limitation, and examples thereof include: for example, ethylene glycol diglycidyl ether, glycerol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, resorcinol glycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, 1,4-butanediol diglycidyl ether, bisphenol A diglycidyl ether, sorbitol polyglycidyl ether, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycerol polyglycidyl ether, or polyglycerol polyglycidyl ether, etc. The epoxy compound (B) used in the present embodiment can be used alone or in combination of two or more. It should be noted that, with respect to the epoxy compound (B), a commercially available product can be used directly, or a product manufactured based on a generally known method can be used.
[0050] The epoxy compound (B) is not particularly limited, but is preferably one or more selected from ethylene glycol diglycidyl ether, glycerol diglycidyl ether, sorbitol polyglycidyl ether, and diglycerol polyglycidyl ether. From the viewpoint of being able to provide an electrolytic capacitor showing low ESR characteristics, sorbitol polyglycidyl ether is more preferred.
[0051] In the conductive polymer solution of the present embodiment, the content of the epoxy compound (B) is preferably 0.001 to 20 mass %, and from the viewpoint of being able to provide an electrolytic capacitor with high capacity and low ESR characteristics, it is more preferably 0.01 to 20 mass %, more preferably 0.1 to 20 mass %, more preferably 0.1 to 15 mass %, more preferably 0.5 to 10 mass %, further preferably 0.5 to 5 mass %, and particularly preferably 0.5 to 3 mass %.
[0052] From the viewpoint of being able to provide an electrolytic capacitor with high capacity and low ESR characteristics, the content of the epoxy compound (B) is preferably 0.1 to 15 parts by mass, more preferably 0.5 to 10 parts by mass, further preferably 0.5 to 5 parts by mass, and particularly preferably 0.5 to 3 parts by mass, relative to 1 part by mass of the polythiophene (A).
[0053] In the conductive polymer solution of this embodiment, the weight average molecular weight of polyacrylic acid (C) is not particularly limited, but is preferably 100 to 1,000,000, more preferably 1,000 to 500,000, further preferably 2,000 to 100,000, and particularly preferably 5,000 to 50,000. This configuration has the advantage of being able to provide an electrolytic capacitor having low ESR characteristics.
[0054] In the conductive polymer solution of the present embodiment, the content of the polyacrylic acid (C) is preferably 0.001 to 20 mass %, more preferably 0.01 to 20 mass %, and even more preferably 0.1 to 20 mass % from the viewpoint of providing an electrolytic capacitor having low ESR characteristics.
[0055] The content of the polyacrylic acid (C) is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 8 parts by mass, and even more preferably 0.3 to 6 parts by mass relative to 1 part by mass of the polythiophene (A). This configuration has the advantage of providing an electrolytic capacitor having low ESR characteristics.
[0056] The compound (D) that can form an ion pair with the above-mentioned sulfonic acid group is not particularly limited, and examples thereof include: alkali metal compounds, ammonia, organic amine compounds, and quaternary ammonium salts. These compounds react with the sulfonic acid group of the above-mentioned polythiophene (A) to form alkali metal ion salts, ammonium ion salts, organic ammonium ion salts, and quaternary ammonium ion salts of the polythiophene (A).
[0057] The alkali metal compound is not particularly limited, and examples thereof include alkali metal chloride compounds (e.g., lithium chloride, potassium chloride, sodium chloride, rubidium chloride, cesium chloride, lithium bromide, potassium bromide, sodium bromide, rubidium bromide, cesium bromide, etc.) or alkali metal hydroxides (e.g., lithium hydroxide, potassium hydroxide, sodium hydroxide, rubidium hydroxide, cesium hydroxide, etc.).
[0058] By incorporating the alkali metal compound into the conductive polymer solution of this embodiment, an alkali metal ion salt of the polythiophene (A) can be prepared. The alkali metal ion is not particularly limited, and examples thereof include lithium ions, potassium ions, sodium ions, rubidium ions, and cesium ions.
[0059] The organic amine compound is not particularly limited, and examples thereof include primary, secondary, or tertiary organic amine compounds having a total carbon number of 1 to 30. More specifically, examples thereof include methylamine, dimethylamine, trimethylamine, ethylamine, triethylamine, n-propylamine, isopropylamine, n-butylamine, hexylamine, ethanolamine, dimethylaminoethanol, methylaminoethanol, diethanolamine, N-methyldiethanolamine, triethanolamine, 3-amino-1,2-propanediol, 3-methylamino-1,2-propanediol, 3-dimethylamino-1,2-propanediol, 2-amino-2-hydroxymethyl-1,3-propanediol, 1,4-butanediamine, triisobutylamine, triisoamylamine, triisooctylamine, imidazole, N-methylimidazole, 1,2-dimethylimidazole, pyridine, picoline, or lutidine.
[0060] Since the conductive polymer solution of the present embodiment contains the organic amine compound, the organic amine compound reacts with the polythiophene (A) to form an organic ammonium ion, and the organic ammonium ion salt of the polythiophene (A) is prepared. As the organic ammonium ion, there is no particular limitation, and examples thereof include primary, secondary, or tertiary organic ammonium ions having a total carbon number of 1 to 30, and more specifically, examples thereof include methylammonium, dimethylammonium, trimethylammonium, ethylammonium, triethylammonium, n-propylammonium, isopropylammonium, n-butylammonium, hexylammonium, 2-hydroxyethylammonium, N,N-dimethyl-N-(2-hydroxyethyl)ammonium, N-methyl-N-(2-hydroxyethyl)ammonium, di(2-hydroxyethyl)ammonium, ammonium, 2,3-dihydroxypropylammonium, N-methyl-N-(2,3-dihydroxypropyl)ammonium, N,N-dimethyl-N-(2,3-dihydroxypropyl)ammonium, 1,4-butanediammonium, triisobutylammonium, triisopentylammonium, triisooctylammonium, imidazolium cation, N-methylimidazolium cation, 1,2-dimethylimidazolium cation, pyridine Ion, methylpyridine ions, or dimethylpyridine ion.
[0061] The quaternary ammonium salt is not particularly limited, and examples thereof include tetramethylammonium chloride, tetraethylammonium chloride, tetra-n-propylammonium chloride, tetra-n-butylammonium chloride, and tetra-n-hexylammonium chloride.
[0062] The conductive polymer solution of one embodiment of the present invention contains the quaternary ammonium salt, and the quaternary ammonium salt reacts with the polythiophene (A) to form a quaternary ammonium ion, thereby preparing a quaternary ammonium ion salt of the polythiophene (A). The quaternary ammonium ion is not particularly limited, and examples thereof include tetramethylammonium ion, tetraethylammonium ion, tetra-n-propylammonium ion, tetra-n-butylammonium ion, or tetra-n-hexylammonium ion.
[0063] As the compound (D) that can form an ion pair with the sulfonic acid group, from the viewpoint of being able to provide an electrolytic capacitor with excellent low ESR, it is preferably an alkali metal hydroxide, ammonia, or a primary, secondary, or tertiary organic amine compound having a total carbon number of 1 to 16. It should be noted that the primary, secondary, or tertiary organic amine compound having a total carbon number of 1 to 16 may include, for example, methylamine, dimethylamine, trimethylamine, ethylamine, triethylamine, n-propylamine, isopropylamine, n-butylamine, hexylamine, ethanolamine, dimethylaminoethanol, methylaminoethanol, diethanolamine, N-methyldiethanolamine, triethanolamine, 3-amino-1,2-propanediol, 3-methylamino-1,2-propanediol, 3-dimethylamino-1,2-propanediol, 1,4-butanediamine, triisobutylamine, triisoamylamine, imidazole, N-methylimidazole, 1,2-dimethylimidazole, pyridine, picoline, or lutidine.
[0064] When the conductive polymer solution of the present embodiment contains the compound (D), a part or all of the polythiophene (A) containing at least one structural unit selected from the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2) interacts with the compound (F) to form a polythiophene (A) containing at least one structural unit selected from the structural unit represented by the following general formula (1') and the structural unit represented by the general formula (2'). That is, the mixture of the polythiophene (A) containing at least one structural unit selected from the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2) and the compound (D) represents the same substance as the polythiophene (A) containing at least one structural unit selected from the structural unit represented by the general formula (1') and the structural unit represented by the general formula (2').
[0065]
[0066] [In the above general formula (1') and general formula (2'), R 2 The definitions and preferred ranges of m and n are the same as those of R shown in the above general formula (1) and general formula (2). 2 The definitions and preferred ranges of m and n are the same. M represents a hydrogen ion, an alkali metal ion, an ammonium ion, an organic ammonium ion or a quaternary ammonium ion.]
[0067] The alkali metal ion, ammonium ion, organic ammonium ion and quaternary ammonium ion in the above-mentioned M are as described above.
[0068] In the conductive polymer solution of this embodiment, the content of the compound (D) that can form an ion pair with the above-mentioned sulfonic acid group is preferably 0.001 to 20 mass %, more preferably 0.01 to 20 mass %, and further preferably 0.1 to 20 mass % from the viewpoint of being able to provide an electrolytic capacitor showing low ESR characteristics.
[0069] The conductive polymer solution of the present embodiment preferably includes sugar alcohol (E). As the above-mentioned sugar alcohol (E), there is no particular limitation, and examples thereof include: for example, erythritol, glycerol, lactitol, maltitol, xylitol, arabitol, mannitol, sorbitol, etc. The sugar alcohol (E) used in the present embodiment can be used alone or in combination of two or more. It should be noted that, with respect to the sugar alcohol (E), a commercial product can be used directly, or a product manufactured by a generally known method can be used.
[0070] The sugar alcohol (E) is preferably mannitol, sorbitol, erythritol, xylitol, or lactitol, and is more preferably sorbitol or mannitol from the viewpoint of providing an electrolytic capacitor having low ESR characteristics.
[0071] In addition, in the conductive polymer solution of the present embodiment, the content of the above-mentioned sugar alcohol (E) is preferably 0.001~20 mass %, and from the viewpoint of being able to provide an electrolytic capacitor showing low ESR characteristics, it is more preferably 0.01~20 mass %, more preferably 0.1~20 mass %, more preferably 1~20 mass %, more preferably 3~20 mass %, further preferably 7~20 mass %, and particularly preferably 12~20 mass %.
[0072] From the viewpoint of excellent chemical stability, the conductive polymer solution of the present embodiment preferably contains a conductive polymer (F) which is a complex of a poly(3,4-ethylenedioxythiophene derivative) containing a structural unit represented by the following general formula (3) and a polyanion.
[0073]
[0074] [In the formula, R 3 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkyl group having 1 to 6 carbon atoms which has a substituent, an alkoxy group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms which has a substituent.]
[0075] The conductive polymer (F) of the present embodiment can be obtained by chemically oxidatively polymerizing a 3,4-ethylenedioxythiophene derivative monomer in water in the presence of a polyanion.
[0076] In the above general formula (3), R 3 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkyl group having 1 to 6 carbon atoms which has a substituent, an alkoxy group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms which has a substituent.
[0077] About R 3From the viewpoint of excellent moisture resistance, it is preferably any one selected from a hydrogen atom, a methoxy group, an ethoxy group, a propoxy group, a butoxy group and a hydroxymethyl group, more preferably a hydrogen atom or a hydroxymethyl group, and further preferably a hydrogen atom.
[0078] The 3,4-ethylenedioxythiophene derivative monomer, which is a source of the structural unit represented by the above general formula, may be polymerized alone or in combination. More preferably, 3,4-ethylenedioxythiophene is used alone.
[0079] The polyanion is not particularly limited, and examples thereof include polystyrene sulfonic acid, polyethylene sulfonic acid, polyallyl sulfonic acid, and metal salts, ammonium salts, and amine salts thereof. Among them, polystyrene sulfonic acid is preferred from the viewpoint of providing an electrolytic capacitor having low ESR characteristics.
[0080] The conductive polymer (F) is preferably a composite of poly(3,4-ethylenedioxythiophene) (PEDOT) and polystyrenesulfonic acid (PSS) (hereinafter referred to as "PEDOT:PSS") from the viewpoint of providing an electrolytic capacitor showing low ESR characteristics, and a commercially available PEDOT:PSS may be used.
[0081] In the conductive polymer solution of the present embodiment, the content of the conductive polymer (F) is preferably 0.001 to 20 parts by mass, more preferably 0.1 to 20 parts by mass, and even more preferably 1 to 20% by mass, relative to 1 part by mass of the polythiophene (A).
[0082] The conductive polymer solution of the present embodiment is not particularly limited as long as it contains water, and may also contain a non-aqueous solvent. As the above-mentioned non-aqueous solvent, there is no particular limitation, and an organic solvent or an electrolyte solution may be cited. It should be noted that the conductive polymer solution in which the solvent is water is also particularly referred to as a conductive polymer aqueous solution.
[0083] Examples of the organic solvent include alcohols, aprotic polar organic solvents, polyols, cyclic sulfones, lactones, etc. Among them, lactones, polyols, etc. can be used as an electrolyte solution.
[0084] It should be noted that polyol is preferably used as the organic solvent. This configuration has the advantage of being able to provide an electrolytic capacitor having a low initial surface resistance value (in other words, low ESR characteristics) and a high withstand voltage.
[0085] Examples of alcohols include, for example, methanol, ethanol, propanol, butanol, methoxyethanol, ethoxyethanol, butoxyethanol, and ethylene glycol. Examples of aprotic polar organic solvents include, for example, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and 1-methyl-2-pyrrolidone. Examples of polyols include, for example, ethylene glycol, propylene glycol, and polyglycerol. Examples of cyclic sulfones include, for example, cyclopentane sulfone. Examples of lactones include, for example, lactones such as γ-butyrolactone.
[0086] The above-mentioned solvent may be a mixed solvent of water and an alcohol and / or an aprotic polar organic solvent. At this time, the content of the alcohol and / or the aprotic polar organic solvent in the conductive polymer solution is preferably 0.001 to 20% by mass, more preferably 0.01 to 15% by mass, and further preferably 0.1 to 10% by mass from the viewpoint of excellent operability.
[0087] The conductive polymer solution of the present embodiment may contain components (G) other than those described above.
[0088] The components (G) other than the above components are not particularly limited, and examples thereof include binders and surfactants.
[0089] The binder is not particularly limited, and examples thereof include polyvinyl alcohol, polyvinyl pyrrolidone, cellulose, a water-soluble polyester resin compound, a water-soluble polyurethane resin compound, and a mixture of an organic acid having two or more carboxyl groups.
[0090] As the water-soluble polyester resin compound, for example, polyethylene terephthalate or polytrimethylene terephthalate, etc., can be mentioned. The water-soluble polyester resin compound can be a self-emulsifying type or a reinforced emulsifying type, and is preferably a self-emulsifying type water-soluble polyester resin compound from the viewpoint of water resistance and solvent resistance.
[0091] The water-soluble polyester resin compound may be Vylonal (registered trademark) manufactured by Toyobo Co., Ltd.; Pesresin (registered trademark) manufactured by Takamatsu Oil & Fats Co., Ltd.; Plascoat (registered trademark) manufactured by Huying Chemical Co., Ltd.; Aron Melt (registered trademark) manufactured by Toagosei Co., Ltd.; Pesresin A (registered trademark) manufactured by Takamatsu Oil & Fats Co., Ltd.; or Watersol (registered trademark) manufactured by DIC Corporation, which are easily commercially available.
[0092] The water-soluble polyester resin compounds may be used alone or in combination of two or more.
[0093] The water-soluble polyurethane resin compound is mainly used as a carbamate resin emulsion for industrial purposes. It can be a self-emulsifying type or a reinforced emulsifying type. From the viewpoint of water resistance and solvent resistance, a self-emulsifying type water-soluble polyurethane resin compound is preferably used. As the self-emulsifying type, anionic, cationic, and nonionic types can be mentioned, any of which can be used. In addition, there is no particular limitation on the water-soluble polyurethane resin compound, and polyether type, polyester type, polycarbonate type, etc. can be mentioned.
[0094] Regarding water-soluble polyurethane resin compounds, for example, those manufactured by Sanyo Chemical Industries, Ltd., under the trade names: UCOAT (registered trademark), Permarin (registered trademark), and UPRENE (registered trademark); those manufactured by Kusumoto Chemicals, Co., Ltd., under the trade name: NeoRez (registered trademark); those manufactured by ADEKA Co., Ltd., under the trade name: ADEKA Bontighter (registered trademark); those manufactured by Meisei Chemical Industries, Ltd., under the trade name: Pascol (registered trademark); and those manufactured by DIC Corporation, under the trade name: Hydrun (registered trademark) are easily available through commercial channels.
[0095] The water-soluble polyurethane resin compounds may be used alone or in combination of two or more.
[0096] The organic acid having two or more carboxyl groups is not particularly limited, and examples thereof include adipic acid and phthalic acid.
[0097] The surfactant is not particularly limited and may be, for example, an anionic surfactant, a cationic surfactant, a nonionic surfactant, an amphoteric surfactant, a fluorine-based surfactant, or a silicone-based surfactant, and more preferably at least one selected from a nonionic surfactant and an amphoteric surfactant.
[0098] The anionic surfactant is not particularly limited, and examples thereof include sodium dodecyl sulfate and sodium dodecylbenzenesulfonate.
[0099] The cationic surfactant is not particularly limited, and a commercially available product may be used, or a separately produced generally known product may be used.
[0100] The nonionic surfactant is not particularly limited, and examples thereof include polyethylene glycol-based surfactants, acetylene glycol-based surfactants, polyol-based surfactants, and polymer-based nonionic surfactants.
[0101] The polyethylene glycol type surfactant is not particularly limited, and examples thereof include higher alcohol ethylene oxide adducts, alkylphenol ethylene oxide adducts, fatty acid ethylene oxide adducts, polyhydric alcohol fatty acid ester ethylene oxide adducts, higher alkylamine ethylene oxide adducts, ethylene oxide adducts of fats and oils, and polypropylene glycol ethylene oxide adducts.
[0102] The acetylene glycol type surfactant is not particularly limited, and examples thereof include 2,4,7,9-tetramethyl-5-decyne-4,7-diol, Surfynol (registered trademark) (manufactured by Air Products), and Olefin (registered trademark) (manufactured by Nissin Chemical Industry Co., Ltd.).
[0103] The polyol surfactant is not particularly limited, and examples thereof include fatty acid esters of glycerol, fatty acid esters of pentaerythritol, fatty acid esters of sorbitol and sorbitan, fatty acid esters of sucrose, alkyl ethers of higher alcohols, and fatty acid amides of alkanolamines.
[0104] The above-mentioned amphoteric surfactant is not particularly limited, and examples thereof include betaine-type amphoteric surfactants. Betaine-type amphoteric surfactants are not particularly limited, and examples thereof include alkyl dimethyl betaine, lauryl dimethyl betaine, stearyl dimethyl betaine, lauryl dihydroxyethyl betaine, and the like.
[0105] The fluorine-based surfactant is not particularly limited as long as it has a perfluoroalkyl group, and examples thereof include Plascoat (registered trademark) RY-2, perfluoroalkane, perfluoroalkyl carboxylic acid, perfluoroalkyl sulfonic acid, and perfluoroalkyl ethylene oxide adducts.
[0106] The above-mentioned silicone-based surfactant is not particularly limited, and examples thereof include: for example, polyether-modified polydimethylsiloxane, polyether-ester-modified polydimethylsiloxane, hydroxyl-containing polyether-modified polydimethylsiloxane, acrylic-containing polyether-modified polydimethylsiloxane, acrylic-containing polyester-modified polydimethylsiloxane, perfluoropolyether-modified polydimethylsiloxane, perfluoropolyester-modified polydimethylsiloxane, or silicone-modified acrylic compounds.
[0107] In addition, a fluorine-based surfactant or a silicone-based surfactant as a leveling agent is effective for improving the flatness of the coating film.
[0108] In the conductive polymer solution of the present embodiment, the content of the component (G) is preferably 0.001 to 20 mass %, more preferably 0.01 to 15 mass %, and even more preferably 0.1 to 10 mass % from the viewpoint of excellent handleability.
[0109] The method for preparing the conductive polymer solution of the present embodiment is not particularly limited, and examples thereof include: for example, a method of mixing a solution or solid of the polythiophene (A) of the present embodiment, an epoxy compound (B), polyacrylic acid (C) as required, sugar alcohol (E), and a conductive polymer (F), and water, and homogenizing by stirring. In this case, the conductive polymer solution may be prepared by adding a compound (D) capable of forming an ion pair with a sulfonic acid group and other additives as required (for example, component (G) etc.), or by the following method: a conductive polymer solution containing polythiophene (A), an epoxy compound (B), polyacrylic acid (C) as required, sugar alcohol (E), and a conductive polymer (F) is temporarily prepared, and then a compound (D) capable of forming an ion pair with a sulfonic acid group and the above-mentioned other additives are added and mixed.
[0110] Here, the temperature during mixing is not particularly limited, and for example, the mixing can be performed at room temperature to under heating, and is preferably 0° C. or higher and 100° C. or lower.
[0111] The atmosphere during mixing is not particularly limited, and may be air or in an inert gas.
[0112] When mixing the conductive polymer solution of the present embodiment, in addition to the general mixing and dissolving operation using a stirrer or a stirring blade, ultrasonic irradiation and homogenization (for example, using a mechanical homogenizer, an ultrasonic homogenizer, a high-pressure homogenizer, etc.) can also be performed. When homogenization is performed, in order to prevent thermal degradation of the polymer, it is preferably performed while cooling.
[0113] The concentration of the conductive polymer solution of the present embodiment can be adjusted by adjusting the blending ratio or by concentrating the solution after blending. The concentration method may be a method of distilling off the solvent under reduced pressure or a method using an ultrafiltration membrane.
[0114] The content of polythiophene (A) in the conductive polymer solution of the present embodiment is not particularly limited as long as it is 0.01 to 10% by mass. It should be noted that since the conductive polymer solution containing polythiophene (A) and epoxy compound (B) of the present invention is dried / dehydrated after coating, a good uniform film can be obtained by controlling the content within the above range.
[0115] The particle size of the solid component in the conductive polymer solution of the present embodiment is not particularly limited, and the smaller the particle size, the better the water solubility, which is also ideal from the perspective of conductivity and forming a uniform film during film formation. For example, when the solid component concentration of the conductive polymer solution prepared at room temperature or under heating is 10% by mass or less, the particle size (D50) of the solid component is preferably 0.02 μm or less.
[0116] The viscosity (20° C.) of the conductive polymer solution of the present embodiment is preferably 200 mPa·s or less, more preferably 100 mPa·s or less, and even more preferably 50 mPa·s or less.
[0117] The conductive polymer film of the present embodiment can be formed using the conductive polymer solution of the present embodiment. The method (manufacturing method) for forming the conductive polymer film of the present embodiment is not particularly limited, and can include, for example, a method including applying the conductive polymer solution of the present embodiment to a substrate and drying the substrate.
[0118] The drying atmosphere may be any of air, inert gas, vacuum, or reduced pressure. From the viewpoint of suppressing degradation of the polymer film, an inert gas such as nitrogen or argon is preferred.
[0119] The substrate is not particularly limited, and examples thereof include glass, plastic, polyester, polyacrylate, polycarbonate, metal oxide, ceramic, and a resist substrate.
[0120] The coating method is not particularly limited, and examples thereof include casting, dipping, bar coating, roll coating, gravure coating, flexographic printing, spray coating, spin coating, and inkjet printing.
[0121] The drying temperature of the coating film is not particularly limited as long as a uniform conductive film can be obtained, but is preferably in the range of room temperature to 300° C., more preferably in the range of room temperature to 250° C., and even more preferably in the range of room temperature to 200° C. In this specification, room temperature refers to 15 to 25° C.
[0122] The thickness of the coating film is not particularly limited, but is preferably 10 -2 ~10 2 The surface resistivity of the obtained coating film is not particularly limited, but is preferably 1 to 10 9 Ω / □ range.
[0123] The electrical conductivity of the conductive polymer film obtained in this embodiment is not particularly limited, but the electrical conductivity (conductivity) in the film state is preferably 10 S / cm or more.
[0124] The conductive polymer film of this embodiment can be used in, for example, antistatic agents, solid electrolytes for electrolytic capacitors, conductive coatings, electrochromic elements, electrode materials, thermoelectric conversion materials, transparent conductive films, chemical sensors, actuators, etc. In particular, it is very useful as a solid electrolyte for electrolytic capacitors. When the conductive polymer film of this embodiment is used for electrolytic capacitors, an electrolytic capacitor having excellent characteristics of maintaining high capacity and having low ESR can be provided.
[0125] In addition, the conductive polymer film of the present embodiment can provide an electrolytic capacitor with a long life, and thus contribute to improving energy efficiency, thereby contributing to the achievement of the Sustainable Development Goals (SDGs).
[0126] The electrolytic capacitor of the present embodiment can be formed using the conductive polymer solution of the present embodiment. As a method for manufacturing the electrolytic capacitor of the present embodiment, a method including the following steps can be cited: covering the surface of the dielectric oxide film of the anode body on which the dielectric oxide film is formed with the conductive polymer solution of the present embodiment, and heating and drying it. More specifically, the method for manufacturing the electrolytic capacitor of the present embodiment can also include: immersing the element including the anode body and the cathode in the conductive polymer solution of the present embodiment, and heating and drying it.
[0127] In this embodiment, the anode body preferably includes a dielectric oxide film (dielectric layer) and an anode. The dielectric layer can also be considered to be composed of an oxide film.
[0128] In the present embodiment, the anode is not particularly limited, but from the viewpoint of facilitating the formation of a dielectric layer, preferably at least one selected from aluminum, tantalum, niobium, and titanium, and more preferably contains aluminum.
[0129] In this embodiment, the oxide film constituting the dielectric layer is preferably formed by oxidation of the anode surface. The method for forming the oxide film on the anode surface (i.e., the method for manufacturing the anode body) is not particularly limited, and examples thereof include a method of oxidizing the anode by applying voltage in a buffer solution.
[0130] In the present embodiment, the cathode is not particularly limited, but is preferably one or more selected from aluminum, silver, tantalum, niobium, and titanium, and more preferably contains aluminum, from the viewpoint of facilitating formation of a dielectric layer.
[0131] The drying temperature in the method for producing the electrolytic capacitor of the present embodiment can refer to the description of the drying temperature of the coating film in the method for forming the conductive polymer film of the present embodiment (production method).
[0132] In the electrolytic capacitor of the present embodiment, the hybrid capacitor can be obtained, for example, by obtaining a solid electrolytic capacitor by the above method and then immersing the solid electrolytic capacitor in an electrolyte solution.
[0133] The solvent used in the above-mentioned electrolyte solution used in the manufacture of the hybrid capacitor is not particularly limited, but from the viewpoint of being difficult to evaporate even at high temperatures, it is preferably one or more selected from γ-butyrolactone, ethylene glycol, propylene glycol, cyclopentane, N-methylacetamide, N,N-dimethylformamide and N-methyl-2-pyrrolidone.
[0134] The present invention is not limited to the above-described embodiments, and various modifications can be made within the scope of the claims. Embodiments obtained by appropriately combining technical solutions disclosed in different embodiments are also included in the technical scope of the present invention.
[0135] One embodiment of the present invention may include the following configurations.
[0136] [1] A conductive polymer solution having a pH of 1.5 to 5.0, the solution comprising:
[0137] Polythiophene (A) 0.01-10 mass%,
[0138] Epoxy compound (B) 0.001 to 20 mass %, and
[0139] water,
[0140] The polythiophene (A) comprises at least one structural unit selected from the structural unit represented by the following general formula (1) and the structural unit represented by the following general formula (2);
[0141] The epoxy compound (B) has at least two epoxy groups.
[0142]
[0143] In the general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1.
[0144] [2] The conductive polymer solution according to [1], further comprising 0.001 to 20 mass % of polyacrylic acid (C).
[0145] [3] The conductive polymer solution according to [1] or [2], further comprising 0.001 to 20% by mass of the compound (D)
[0146] The compound (D) can form an ion pair with the sulfonic acid group of the polythiophene (A).
[0147] [4] The conductive polymer solution according to any one of [1] to [3], wherein
[0148] The content of the epoxy compound (B) is 0.1 to 15 parts by mass based on 1 part by mass of the polythiophene (A).
[0149] [5] The conductive polymer solution according to [2], wherein
[0150] The content of the polyacrylic acid (C) is 0.1 to 10 parts by mass based on 1 part by mass of the polythiophene (A).
[0151] [6] The conductive polymer solution according to any one of [1] to [5], further comprising 0.001 to 20% by mass of a sugar alcohol (E).
[0152] [7] The conductive polymer solution according to [6], wherein
[0153] The sugar alcohol (E) is sorbitol, mannitol, erythritol, xylitol or lactitol.
[0154] [8] The conductive polymer solution according to any one of [1] to [7], further comprising a conductive polymer (F), wherein:
[0155] The conductive polymer (F) is a complex of a polyanion and a poly(3,4-ethylenedioxythiophene derivative) containing a structural unit represented by the following general formula (3),
[0156] The content of the conductive polymer (F) is 0.001 to 20 parts by mass relative to 1 part by mass of the polythiophene (A).
[0157]
[0158] In the formula, R 3 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkyl group having 1 to 6 carbon atoms which has a substituent, an alkoxy group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms which has a substituent.
[0159] [9] The conductive polymer solution according to [8], wherein
[0160] R 3 A hydrogen atom.
[0161]
[10] The conductive polymer solution according to [8], wherein
[0162] The conductive polymer (F) is PEDOT:PSS.
[0163]
[11] A method for producing a conductive polymer film, the method comprising:
[0164] A step of applying the conductive polymer solution according to any one of [1] to
[10] to a substrate and drying the substrate.
[0165]
[12] A method for manufacturing an electrolytic capacitor, the method comprising:
[0166] A step of coating the surface of the dielectric oxide film of the anode body on which the dielectric oxide film is formed with the conductive polymer solution described in any one of [1] to
[10] , and heating and drying the surface.
[0167] Example
[0168] Hereinafter, the present invention will be described in detail based on Examples, but the present invention is not to be construed as being limited thereto.
[0169] It should be noted that the analytical instrument and measurement method used in this example are as follows.
[0170] [NMR measurement]
[0171] Device: VARIAN, Gemini-200
[0172] [Measurement of electrical conductivity of polythiophene (A)]
[0173] 0.5 ml of an aqueous solution containing PEDOT-MPS (corresponding to the polythiophene (A) of the present invention) was applied to a 25 mm square alkali-free glass plate, and heated on a hot plate at 60° C. for 30 minutes and further at 200° C. for 60 minutes in air to obtain a conductive polymer film.
[0174] Regarding the above-mentioned conductive polymer film, a notch was opened with a pitch interval of 6.25 mm in the x direction and 6.25 mm in the y direction to expose the glass part, and the film thickness at 9 points of the measurement position was measured in an atmosphere of 25°C and 50%RH. As a measuring device, DEKTAK XT manufactured by BRUKER was used. In addition, the surface resistivity of the above-mentioned 9 points of the measurement position was measured in an atmosphere of 25°C and 50%RH. As a measuring device, a surface resistivity measuring instrument Loresta GP MCP-T600 manufactured by Mitsubishi Chemical Corporation was used, and the measuring probe was ASP.
[0175] The electrical conductivity was calculated according to the following formula from the film thickness and surface resistivity of the conductive polymer film measured by the above-mentioned measuring method.
[0176] Conductivity [S / cm] = 10 4 / (Surface resistivity [Ω / □] × film thickness [μm])
[0177] [Manufacturing of solid electrolytic capacitors]
[0178] Aluminum foil was welded to a portion of etched aluminum foil with a thickness of 100 μm and a lead wire (anode) was installed. The etched aluminum foil was immersed in an aqueous solution of ammonium dihydrogen phosphate at a temperature of 80°C and a concentration of 0.2 wt%, and a DC voltage of 130 V was applied for 20 minutes to form a dielectric layer (anode body) containing aluminum oxide (i.e., aluminum oxide film) on the surface of the anode.
[0179] In addition, an aluminum foil with a thickness of 50 μm and an etching treatment with lead wires installed was used as a cathode, and a separator made of insulating paper was inserted between the anode body and the cathode to produce a wound winding element. Then, the winding element was immersed in a conductive polymer solution described below and taken out, and then dried at 150° C. for 30 minutes to produce an unsealed solid electrolytic capacitor element.
[0180] [Manufacturing of Hybrid Capacitors]
[0181] The solid electrolytic capacitor element produced by the above method was immersed in a γ-butyrolactone-based electrolyte to obtain an unsealed hybrid capacitor element.
[0182] [Capacitor element characteristic measurement]
[0183] Device: LCR Meter IM3536 manufactured by Hioki Electric Co., Ltd.
[0184] The characteristics of the solid electrolytic capacitor element and the hybrid capacitor element produced by the above method were evaluated by using the above-mentioned apparatus for initial capacitance [μF] at 120 Hz and initial ESR [mΩ] at 100 kHz.
[0185] Here, for the "solid electrolytic capacitor", when the initial capacity [μF] at 120 Hz is 103 μF or more, it is determined that the "solid electrolytic capacitor has a high capacity".
[0186] In addition, for the "solid electrolytic capacitor", when the initial ESR [mΩ] at 100 kHz was 12.0 mΩ or less, it was determined that the "solid electrolytic capacitor showed low ESR characteristics".
[0187] Furthermore, the above-mentioned "hybrid capacitor element" was left at 260° C. for 10 minutes or at 150° C. for 150 hours, and the capacitance [μF] at 120 Hz and the ESR [mΩ] at 100 kHz after these operations were evaluated.
[0188] It should be noted that the inventors found that when the 120Hz capacity [μF] and 100kHz ESR [mΩ] of the "hybrid capacitor element" after being placed at 260°C for 10 minutes are good values, the high capacity and low ESR characteristics can be maintained for a long time (hundreds of hours) at a temperature lower than 260°C (generally about 150°C). Therefore, in this embodiment, the following situations are judged as "the hybrid capacitor can maintain low ESR characteristics for a long time": the 100kHz ESR [mΩ] of the "hybrid capacitor element" after being placed at 260°C for 10 minutes measured by the above method is less than 20mΩ; or the ESR change rate (R / R0) is less than 1.50. In addition, the 120Hz capacity [μF] of the "hybrid capacitor element" after being placed at 260°C for 10 minutes measured by the above method is 104μF or more, which is judged as "the hybrid capacitor can maintain high capacity for a long time".
[0189] In addition, the inventors found that when the 120 Hz capacity [μF] and 100 kHz ESR [mΩ] of the "hybrid capacitor element" after being placed at 150°C for 150 hours are good values, the high capacity and low ESR characteristics can be maintained for a long time (hundreds of hours) at a temperature lower than 150°C. Therefore, in this embodiment, the following cases are judged as "the hybrid capacitor can maintain low ESR characteristics for a long time": the case where the 100 kHz ESR [mΩ] of the "hybrid capacitor element" after being placed at 150°C for 150 hours measured by the above method is 20 mΩ or less; or the case where the ESR change rate (R / R0) is 1.50 or less. In addition, the case where the 120 Hz capacity [μF] of the "hybrid capacitor element" after being placed at 150°C for 150 hours measured by the above method is 104 μF or more is judged as "the hybrid capacitor can maintain high capacity for a long time".
[0190] Synthesis example 1
[0191] According to Synthesis Example 1 and Synthesis Example 2 of the known document (Japanese Patent Publication No. 2019-196443), poly(3-[(2,3-dihydrothieno[3,4-b]-[1,4] ... An aqueous solution of [(1-(2-(((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((((
[0192]
[0193] Example 1
[0194] (Preparation of Conductive Polymer Solution)
[0195] The aqueous solution of PEDOT-MPS obtained in Synthesis Example 1 was dehydrated under reduced pressure to adjust to an aqueous solution containing 1.56% by mass of PEDOT-MPS. 4.44 g of a 45% polyacrylic acid aqueous solution (AQUALIC HL415 manufactured by Nippon Shokubai), 1.0 g of ethylene glycol diglycidyl ether (manufactured by Tokyo Chemical Industry) as an epoxy compound (B), 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Chemical Industry) and 10.5 g of water were added to 64.1 g of the aqueous solution containing 1.56% by mass of PEDOT-MPS, and stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were produced by the above-mentioned method using the above-mentioned conductive polymer solution, and their characteristics were evaluated. The evaluation results are shown in Tables 1, 3 and 5.
[0196] Example 2
[0197] To 64.1 g of the aqueous solution containing 1.56% PEDOT-MPS, 4.44 g of a 45% polyacrylic acid aqueous solution (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai), 2.0 g of ethylene glycol diglycidyl ether (manufactured by Tokyo Chemical Industry) as an epoxy compound (B), 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Chemical Industry), and 9.45 g of water were added and stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were prepared using the conductive polymer solution according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 1, 3, and 5.
[0198] Example 3
[0199] To the above aqueous solution containing 1.56 mass % PEDOT-MPS 64.1g, 45% polyacrylic acid aqueous solution (AQUALIC HL415 manufactured by Nippon Shokubai) 4.44g, 1.0g of glycerol diglycidyl ether (manufactured by Sigma-Aldrich) as an epoxy compound (B), 20.0g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Pharmaceutical) and 10.5g of water were added and stirred and mixed. Next, 0.3g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 3. Relative to 1 mass part of PEDOT-MPS, 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 mass parts. The above conductive polymer solution was used to prepare solid electrolytic capacitor elements and hybrid capacitor elements according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 1, 3 and 5.
[0200] Example 4
[0201] To the above aqueous solution containing 1.56 mass % PEDOT-MPS 64.1g, 45% polyacrylic acid aqueous solution (AQUALIC HL415 manufactured by Nippon Shokubai) 4.44g, 2.0g of glycerol diglycidyl ether (manufactured by Sigma-Aldrich) as an epoxy compound (B), 20.0g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Pharmaceuticals), and 9.45g of water were added and stirred and mixed. Next, 0.3g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 3. Relative to 1 mass part of PEDOT-MPS, 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 mass parts. The above conductive polymer solution was used to prepare solid electrolytic capacitor elements and hybrid capacitor elements according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 1, 3 and 5.
[0202] Example 5
[0203] To 64.1 g of the aqueous solution containing 1.56% PEDOT-MPS by mass, 45% polyacrylic acid aqueous solution (AQUALIC HL415 manufactured by Nippon Shokubai) 4.44 g, sorbitol polyglycidyl ether (DENACOL EX-614B manufactured by Nagase ChemteX) 2.0 g as an epoxy compound (B), polyglycerol (polyglycerol #310 manufactured by Sakamoto Pharmaceutical) 20.0 g, and water 9.45 g were added and stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 3. 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were prepared using the conductive polymer solution according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 1, 3 and 5.
[0204] Example 6
[0205] In Example 4, after adding 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol and stirring and mixing, 300 g of 1.2% PEDOT:PSS aqueous dispersion was further added and stirred and mixed. In addition, solid electrolytic capacitor elements and hybrid capacitor elements were prepared according to Example 4, and the characteristics were evaluated. The evaluation results are shown in Tables 1, 3 and 5.
[0206] Example 7
[0207] To 64.1 g of the aqueous solution containing 1.56% PEDOT-MPS by mass, 4.44 g of a 45% polyacrylic acid aqueous solution (AQUALIC HL415 manufactured by Nippon Shokubai), 2.0 g of diglycerol polyglycidyl ether (DENACOL EX-421 manufactured by Nagase ChemteX) as an epoxy compound (B), 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Pharmaceuticals), and 9.45 g of water were added and stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were prepared using the conductive polymer solution according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 1, 3, and 5.
[0208] Example 8
[0209] To 64.1 g of the aqueous solution containing 1.56% PEDOT-MPS, 4.44 g of a 45% polyacrylic acid aqueous solution (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai), 5.0 g of ethylene glycol diglycidyl ether (manufactured by Tokyo Chemical Industry) as an epoxy compound (B), 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Chemical Industry), and 6.45 g of water were added and stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were prepared using the conductive polymer solution according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 1, 3, and 5.
[0210] Example 9
[0211] To 64.1 g of the aqueous solution containing 1.56% PEDOT-MPS, 4.44 g of a 45% polyacrylic acid aqueous solution (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai), 10.0 g of ethylene glycol diglycidyl ether (manufactured by Tokyo Chemical Industry) as an epoxy compound (B), 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Chemical Industry), and 1.45 g of water were added and stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were prepared using the conductive polymer solution according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 1, 3, and 5.
[0212] Example 10
[0213] To 64.1 g of the aqueous solution containing 1.56% by mass of PEDOT-MPS, 4.44 g of a 45% polyacrylic acid aqueous solution (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai), 2.0 g of ethylene glycol diglycidyl ether (manufactured by Tokyo Chemical Industry) as an epoxy compound (B), 5.00 g of sorbitol (manufactured by Fuji Film Wako Pure Chemical Industries) as a sugar alcohol (E), 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Chemical Industries), and 4.45 g of water were added and stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were produced by the above-mentioned method using the above-mentioned conductive polymer solution, and their characteristics were evaluated. The evaluation results are shown in Tables 1, 3 and 5.
[0214] Embodiment 11
[0215] To 64.1 g of the aqueous solution containing 1.56% by mass of PEDOT-MPS, 4.44 g of a 45% polyacrylic acid aqueous solution (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai), 2.0 g of ethylene glycol diglycidyl ether (manufactured by Tokyo Chemical Industry) as an epoxy compound (B), 9.00 g of sorbitol (manufactured by Fuji Film Wako Pure Chemical Industries) as a sugar alcohol (E), 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Chemical Industries), and 0.45 g of water were added and stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were produced by the above-mentioned method using the above-mentioned conductive polymer solution, and their characteristics were evaluated. The evaluation results are shown in Tables 1, 3 and 5.
[0216] Example 12
[0217] To 50.0 g of the aqueous solution containing 2.00% by mass of PEDOT-MPS, 4.44 g of a 45% polyacrylic acid aqueous solution (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai), 2.0 g of ethylene glycol diglycidyl ether (manufactured by Tokyo Chemical Industry) as an epoxy compound (B), 15.00 g of sorbitol (manufactured by Fuji Film Wako Pure Chemical Industries) as a sugar alcohol (E), 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Chemical Industries), and 8.56 g of water were added and stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were produced by the above-mentioned method using the above-mentioned conductive polymer solution, and their characteristics were evaluated. The evaluation results are shown in Tables 1, 3 and 5.
[0218] Example 13
[0219] To 64.1 g of the aqueous solution containing 1.56% by mass of PEDOT-MPS, 4.44 g of a 45% polyacrylic acid aqueous solution (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai), 2.0 g of ethylene glycol diglycidyl ether (manufactured by Tokyo Chemical Industry) as an epoxy compound (B), 9.00 g of mannitol (manufactured by Fuji Film Wako Pure Chemical Industries) as a sugar alcohol (E), 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Chemical Industries), and 0.45 g of water were added and stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were produced by the above-mentioned method using the above-mentioned conductive polymer solution, and their characteristics were evaluated. The evaluation results are shown in Tables 1, 3 and 5.
[0220] Embodiment 14
[0221] To 64.1 g of the aqueous solution containing 1.56% by mass of PEDOT-MPS, 4.44 g of a 45% polyacrylic acid aqueous solution (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai), 2.0 g of ethylene glycol diglycidyl ether (manufactured by Tokyo Chemical Industry) as an epoxy compound (B), 9.00 g of erythritol (manufactured by Fuji Film Wako Pure Chemical Industries) as a sugar alcohol (E), 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Chemical Industries), and 0.45 g of water were added and stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were produced by the above-mentioned method using the above-mentioned conductive polymer solution, and their characteristics were evaluated. The evaluation results are shown in Tables 1, 3 and 5.
[0222] Embodiment 15
[0223] To 64.1 g of the aqueous solution containing 1.56% by mass of PEDOT-MPS, 4.44 g of a 45% polyacrylic acid aqueous solution (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai), 2.0 g of ethylene glycol diglycidyl ether (manufactured by Tokyo Chemical Industry) as an epoxy compound (B), 9.00 g of xylitol (manufactured by Fuji Film Wako Pure Chemical Industries) as a sugar alcohol (E), 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Chemical Industries), and 0.45 g of water were added and stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were produced by the above-mentioned method using the above-mentioned conductive polymer solution, and their characteristics were evaluated. The evaluation results are shown in Tables 1, 3 and 5.
[0224] Example 16
[0225] To 64.1 g of the aqueous solution containing 1.56% by mass of PEDOT-MPS, 4.44 g of a 45% polyacrylic acid aqueous solution (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai), 2.0 g of ethylene glycol diglycidyl ether (manufactured by Tokyo Chemical Industry) as an epoxy compound (B), 9.00 g of lactitol (manufactured by Fuji Film Wako Pure Chemical Industries) as a sugar alcohol (E), 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Chemical Industries), and 0.45 g of water were added and stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were produced by the above-mentioned method using the above-mentioned conductive polymer solution, and their characteristics were evaluated. The evaluation results are shown in Tables 1, 3 and 5.
[0226] Embodiment 17
[0227] To the aqueous solution 64.1g containing 1.56% by mass of PEDOT-MPS, 2.0g of ethylene glycol diglycidyl ether (Tokyo Chemical) as an epoxy compound (B), 20.0g of polyglycerol (polyglycerol #310 made by Sakamoto Pharmaceuticals), and 13.9g of water were added and stirred and mixed. Next, 0.3g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 3. Relative to 1 part by mass of PEDOT-MPS, 2-amino-2-hydroxymethyl-1,3-propanediol is 0.3 parts by mass. The above-mentioned conductive polymer solution was used to prepare solid electrolytic capacitor elements and hybrid capacitor elements according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 1, 3 and 5.
[0228] Embodiment 18
[0229] To 64.1 g of the aqueous solution containing 1.56% PEDOT-MPS, 4.44 g of a 45% polyacrylic acid aqueous solution (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai), 2.0 g of ethylene glycol diglycidyl ether (manufactured by Tokyo Chemical Industry) as an epoxy compound (B), 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Chemical Industry), and 9.45 g of water were added and stirred and mixed. Next, 0.25 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 2. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.25 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were prepared using the conductive polymer solution according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 1, 3, and 5.
[0230] Embodiment 19
[0231] To 64.1 g of the aqueous solution containing 1.56% by mass of PEDOT-MPS, 4.44 g of a 45% polyacrylic acid aqueous solution (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai), 2.0 g of ethylene glycol diglycidyl ether (manufactured by Tokyo Chemical Industry) as an epoxy compound (B), 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Chemical Industry), and 9.45 g of water were added and stirred and mixed. Next, 0.4 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 5. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.4 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were prepared using the conductive polymer solution according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 1, 3, and 5.
[0232] Comparative Example 1
[0233] 35.9 g of water was added to 64.1 g of the aqueous solution containing 1.56% by mass of PEDOT-MPS, and the mixture was stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and the mixture was stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were prepared using the conductive polymer solution according to the above method, and their characteristics were evaluated. The evaluation results are shown in Tables 2, 4, and 6.
[0234] Comparative Example 2
[0235] 16.7 g of water was added to 83.3 g of 1.2% PEDOT:PSS aqueous dispersion and stirred to mix. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixture and stirred to mix to obtain a conductive polymer aqueous dispersion with a pH of 3. Relative to 1 part by mass of PEDOT:PSS, 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass. Solid electrolytic capacitor elements and hybrid capacitor elements were prepared using the above conductive polymer aqueous dispersion according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 2, 4 and 6.
[0236] Comparative Example 3
[0237] To 83.3 g of 1.2% PEDOT:PSS aqueous dispersion was added 2.0 g of ethylene glycol diglycidyl ether (manufactured by Tokyo Chemical Industry) as an epoxy compound (B) and 14.7 g of water, and stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer aqueous dispersion with a pH of 3. Relative to 1 part by mass of PEDOT:PSS, 2-amino-2-hydroxymethyl-1,3-propanediol is 0.3 parts by mass. Solid electrolytic capacitor elements and hybrid capacitor elements were prepared using the above-mentioned conductive polymer aqueous dispersion according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 2, 4 and 6.
[0238] Comparative Example 4
[0239] To 64.1 g of the aqueous solution containing 1.56% PEDOT-MPS by mass, 45% polyacrylic acid aqueous solution (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai) 4.44 g, 3-glycidyloxypropyltrimethoxysilane (manufactured by Tokyo Chemical Industry, monoepoxy compound) 2.0 g, polyglycerol (polyglycerol #310 manufactured by Sakamoto Pharmaceutical) 20.0 g, and water 9.45 g were added and stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were prepared using the conductive polymer solution according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 2, 4, and 6.
[0240] Comparative Example 5
[0241] To 64.1 g of the aqueous solution containing 1.56 mass % of PEDOT-MPS, 4.44 g of a 45% aqueous solution of polyacrylic acid (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai) and lauryl alcohol (EO) were added. 15 2.0 g of glycidyl ether (DENACOL EX-171 manufactured by NagaseChemteX, a monoepoxy compound), 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Pharmaceuticals), and 9.45 g of water were stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution and stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were prepared using the conductive polymer solution according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 2, 4, and 6.
[0242] Comparative Example 6
[0243] To 64.1 g of the aqueous solution containing 1.56 mass % of PEDOT-MPS was added lauryl alcohol (EO). 15 2.0 g of glycidyl ether (DENACOL EX-171 manufactured by Nagase ChemteX, a monoepoxy compound), 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Pharmaceuticals), and 13.9 g of water were stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution and stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were prepared using the conductive polymer solution according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 2, 4, and 6.
[0244] Comparative Example 7
[0245] To 64.1 g of the aqueous solution containing 1.56% PEDOT-MPS, 45% polyacrylic acid aqueous solution (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai) 4.44 g, phenol (EO) 5 glycidyl ether (DENACOL EX-145 manufactured by Nagase ChemteX, monoepoxy compound) 2.0 g, polyglycerol (polyglycerol #310 manufactured by Sakamoto Pharmaceutical) 20.0 g, and water 9.45 g were added and stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were prepared according to the above method using the conductive polymer solution, and the characteristics were evaluated. The evaluation results are shown in Tables 2, 4 and 6.
[0246] Comparative Example 8
[0247] To 64.1 g of the aqueous solution containing 1.56% PEDOT-MPS, 45% polyacrylic acid aqueous solution (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai) 4.44 g, 1,2-butylene oxide (manufactured by Fuji Film Wako Pure Chemicals, monoepoxy compound) 2.0 g, polyglycerol (polyglycerol #310 manufactured by Sakamoto Pharmaceutical) 20.0 g, and water 9.45 g were added and stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were prepared using the conductive polymer solution according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 2, 4, and 6.
[0248] Comparative Example 9
[0249] To 64.1 g of the aqueous solution containing 1.56% PEDOT-MPS, 45% polyacrylic acid aqueous solution (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai) 4.44 g, 2,3-epoxy-1-propanol (manufactured by Fuji Film Wako Pure Chemicals, monoepoxy compound) 2.0 g, polyglycerol (polyglycerol #310 manufactured by Sakamoto Pharmaceutical) 20.0 g, and water 9.45 g were added and stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were prepared using the conductive polymer solution according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 2, 4, and 6.
[0250] Comparative Example 10
[0251] 4.44 g of a 45% polyacrylic acid aqueous solution (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai) and 2.0 g of ethylene glycol diglycidyl ether (manufactured by Tokyo Chemical Industry) as an epoxy compound (B) and 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Chemical Industry) and 9.45 g of water were added to 64.1 g of the aqueous solution containing 1.56% by mass of PEDOT-MPS, and stirred and mixed to obtain a conductive polymer solution with a pH of 1.2. The conductive polymer solution was used to prepare a solid electrolytic capacitor element and a hybrid capacitor element according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 2, 4, and 6.
[0252] Comparative Example 11
[0253] To 64.1 g of the aqueous solution containing 1.56% PEDOT-MPS, 4.44 g of a 45% polyacrylic acid aqueous solution (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai), 2.0 g of ethylene glycol diglycidyl ether (manufactured by Tokyo Chemical Industry) as an epoxy compound (B), 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Chemical Industry), and 9.45 g of water were added and stirred and mixed. Next, 0.55 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 7. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.55 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were prepared using the conductive polymer solution according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 2, 4, and 6.
[0254] Comparative Example 12
[0255] To 64.1 g of the aqueous solution containing 1.56% PEDOT-MPS, 4.44 g of a 45% polyacrylic acid aqueous solution (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai), 2.0 g of ethylene glycol diglycidyl ether (manufactured by Tokyo Chemical Industry) as an epoxy compound (B), 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Chemical Industry), and 9.45 g of water were added and stirred and mixed. Next, 0.9 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution, and stirred and mixed to obtain a conductive polymer solution with a pH of 10. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.9 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were prepared using the conductive polymer solution according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 2, 4, and 6.
[0256] Comparative Example 13
[0257] To 64.1 g of the aqueous solution containing 1.56 mass % of PEDOT-MPS, 4.44 g of a 45% aqueous solution of polyacrylic acid (AQUALIC HL415 (weight average molecular weight 10,000) manufactured by Nippon Shokubai) and 1,1-diol (EO) were added. 15 4.0 g of glycidyl ether (DENACOL EX-171 manufactured by Nagase ChemteX, a monoepoxy compound), 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Pharmaceuticals), and 7.45 g of water were stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution and stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were prepared using the conductive polymer solution according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 2, 4, and 6.
[0258] Comparative Example 14
[0259] To 64.1 g of the aqueous solution containing 1.56 mass % of PEDOT-MPS, 4.44 g of a 45% aqueous solution of polyacrylic acid (AQUALIC HL415 (weight average molecular weight 10000) manufactured by Nippon Shokubai) and lauryl alcohol (EO) were added. 1510.0 g of glycidyl ether (DENACOL EX-171 manufactured by NagaseChemteX, a monoepoxy compound), 20.0 g of polyglycerol (polyglycerol #310 manufactured by Sakamoto Pharmaceuticals), and 1.45 g of water were stirred and mixed. Next, 0.3 g of 2-amino-2-hydroxymethyl-1,3-propanediol was added to the obtained mixed solution and stirred and mixed to obtain a conductive polymer solution with a pH of 3. The amount of 2-amino-2-hydroxymethyl-1,3-propanediol was 0.3 parts by mass relative to 1 part by mass of PEDOT-MPS. Solid electrolytic capacitor elements and hybrid capacitor elements were prepared using the conductive polymer solution according to the above method, and the characteristics were evaluated. The evaluation results are shown in Tables 2, 4, and 6.
[0260]
[0261]
[0262]
[0263]
[0264] The results shown in Tables 1 and 2 show that the addition of the epoxy compound (B) enables Examples 1 to 19 using the conductive polymer solution of the present embodiment to provide solid electrolytic capacitors having high capacitance and low ESR characteristics.
[0265] In addition, it can be seen from the results shown in Tables 3 and 4 that after being placed at 260°C for 10 minutes, Examples 1 to 19 have achieved the effect of suppressing the decrease in capacity and the increase in ESR of the hybrid capacitor. In addition, it can be seen from the results shown in Tables 5 and 6 that after being placed at 150°C for 150 hours, Examples 1 to 19 have achieved the effect of being able to maintain the high capacity and low ESR characteristics of the hybrid capacitor for a long time. It is speculated that this effect is the result of the dissolution of the conductive polymer film in the electrolyte being suppressed by the epoxy compound (B). In contrast, Comparative Examples 1 to 3 cannot have both the high capacity and low ESR characteristics of the hybrid capacitor. As shown in Comparative Examples 10 to 12, when the pH is not 1.5 to 5.0, the high capacity and low ESR characteristics of the hybrid capacitor cannot be achieved. In addition, Comparative Examples 4 to 9, Comparative Example 13 or Comparative Example 14 use monoepoxy compounds, and as a result, the hybrid capacitor cannot have both high capacity and low ESR characteristics. It is speculated that because it is a monoepoxy body, a cross-linked structure is not formed.
[0266] Furthermore, from the results shown in Tables 1 and 2, it can be seen that, by adding the sugar alcohol (E), Examples 10 to 16 achieved the effect of being able to further reduce the ESR in the case of the solid electrolytic capacitor.
[0267] Industrial Applicability
[0268] As described above, when the conductive polymer solution of the present embodiment is used, an electrolytic capacitor having a high capacity and low ESR characteristics can be provided, compared to the case where a conventional conductive polymer solution is used.
Claims
1. A conductive polymer solution having a pH of 1.5 to 5.0, the solution comprising: Polythiophene (A) 0.01-10 mass%, Epoxy compound (B) 0.001 to 20 mass %, and water, in, The polythiophene (A) comprises at least one structural unit selected from the structural unit represented by the following general formula (1) and the structural unit represented by the following general formula (2); The epoxy compound (B) has at least two epoxy groups. In the general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1. 2 . The conductive polymer solution according to claim 1 , further comprising 0.001 to 20% by mass of polyacrylic acid (C).
3. The conductive polymer solution according to claim 1, further comprising 0.001 to 20% by mass of compound (D). in, The compound (D) may form an ion pair with the sulfonic acid group of the polythiophene (A).
4. The conductive polymer solution according to claim 1, wherein The content of the epoxy compound (B) is 0.1 to 15 parts by mass based on 1 part by mass of the polythiophene (A).
5. The conductive polymer solution according to claim 2, wherein The content of the polyacrylic acid (C) is 0.1 to 10 parts by mass based on 1 part by mass of the polythiophene (A). 6 . The conductive polymer solution according to claim 1 , further comprising 0.001 to 20% by mass of sugar alcohol (E).
7. The conductive polymer solution according to claim 6, wherein The sugar alcohol (E) is sorbitol, mannitol, erythritol, xylitol or lactitol.
8. The conductive polymer solution according to claim 1, further comprising a conductive polymer (F), wherein: The conductive polymer (F) is a complex of a poly(3,4-ethylenedioxythiophene derivative) containing a structural unit represented by the following general formula (3) and a polyanion, The content of the conductive polymer (F) is 0.001 to 20 parts by mass relative to 1 part by mass of the polythiophene (A). In the formula, R 3 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkyl group having 1 to 6 carbon atoms which has a substituent, an alkoxy group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms which has a substituent.
9. The conductive polymer solution according to claim 8, wherein R 3 A hydrogen atom.
10. The conductive polymer solution according to claim 8, wherein The conductive polymer (F) is PEDOT:PSS.
11. A method for producing a conductive polymer film, the method comprising: A step of applying the conductive polymer solution according to any one of claims 1 to 10 onto a substrate and drying the substrate.
12. A method for manufacturing an electrolytic capacitor, the method comprising: A step of covering the surface of the dielectric oxide film of the anode body on which the dielectric oxide film is formed with the conductive polymer solution according to any one of claims 1 to 10, and heating and drying the surface.
Citation Information
Patent Citations
Aqueous conductive polymer solution and conductive polymer film
JP2019196443A
Conductive polymer aqueous solution and conductive polymer film
JP2020007519A
Cited By
Electrolyte solution for aluminum electrolytic capacitor and application of electrolyte solution in high-capacitance solid aluminum electrolytic capacitor
CN121122922A
An electrolyte solution for aluminum electrolytic capacitors and its application in high-capacitance solid aluminum electrolytic capacitors.
CN121122922B